Genetic types of carbonate shoal reservoirs in the Middle Triassic of the Sichuan Basin (SW China). (January 2019) - Ding, Xiong; Wu, Han; Sun, Yuefeng; Yu, Hanghang; Zhao, Zihao; Chen, Jingshan; Tang, Qingsong
Abstract: Carbonate shoal reservoirs of the Middle Triassic Leikoupo Formation in the Sichuan Basin were investigated for potential gas resources. The carbonate shoal reservoirs can be divided on the basis of their formation mechanism into residual intergranular pore, karst (further divided into syndepositional-, burial-, and epigenetic-karstification types), dolomitized, and composite reservoirs. Residual intergranular pores and dissolved pores are the main reservoir spaces in the residual intergranular pore reservoirs. Isolated intragranular corroded pores and moldic pores are the main reservoir spaces in syndepositional-karstification reservoirs, the main spaces in burial-karstification reservoirs are dissolved pores and holes, and pores and caves on various scales are the main reservoir spaces of epigenetic-karstification reservoirs. Intercrystal pores and intercrystal solution pores are the main reservoir spaces of dolomitized reservoirs. Composite reservoirs are characterized by a variety of reservoir spaces with pores, holes, and fissures. High-quality shoal reservoirs were formed by superposition of carbonate shoals and constructive diagenetic modification. Preservation of residual intergranular pores was crucial for development of residual intergranular pore reservoirs. Platform-interior micro-highlands, relative declines in sea level, and rainfall controlled the development of syndepositional-karstification reservoirs. Dissolution by unsaturated acidic fluids, pre-existing pores and pore throats, and the direction of corrosive fluid flow were important for burial-karstification reservoirs. Epigenetic-karstification reservoirs formed as a result of significant sea-level drops or tectonic movement. Dolomitized reservoirs formed in shoals affected by dolomitization caused by evaporation of seawater or that occurred during burial. Composite shoal reservoirs were formed by two or more processes. Highlights: Carbonate shoal reservoirs developed in the Middle Triassic of the Sichuan basin. Residual intergranular, karst, dolomitized, and composite pores were identified. Preservation of residual intergranular pores was beneficial for high-quality reservoirs. Minerals in shoals can be dissolved by syndepositional, burial, and epigenetic karstification. Dolomitization with equal-volume metasomatism can enhance shoal reservoir ability.